تأثير الطابق النبتي المتوسطي على بعض الصفات الشكلية لنوع السنديان البلوطي Quercus infectoria Oliv. المنتشر في محافظة اللاذقية (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
أجريت هذا الدراسة في خمسة مواقع مختلفة الارتفاع عن سطح البحر تمثل الطوابق النبتية المتوسطية الموجودة في المنطقة الساحلية  بمحافظة اللاذقية خلال عامي 2009 – 2010م على نوع السنديان البلوطي Quercus infectoria Oliv.، هذا البحث أظهر تأثير الطابق النبتي المتوسطي على الأشجار المدروسة في المواقع المختلفة وظهرت فروق معنوية في الصفات المتعلقة بارتفاع الشجرة وقطرها، طول الجذع الرئيس حتى نقطة التفرع ، عدد الأغصان الرئيسية المتفرعة عن الجذع الرئيسي، طول الثمرة وقطرها، وزن الثمار والأقماع، طول النورة الهرية، عدد الأزهار في النورة الواحدة، طول الورقة، عرضها، مساحة الورقة، التغطية الشجرية، الوزن الرطب والجاف للأوراق. بينما لم يظهر أي تأثير للطابق النبتي المتوسطي ولم يلاحظ وجود فروق معنوية في الصفات المتعلقة بارتفاع القمع، قطره، النسبة المئوية لرطوبة الأوراق، مدة الإزهار. يمكن الاستنتاج بأنه توجد تغيرات في النمو الخضري في الأشجار المدروسة في المواقع المختلفة تبدو وكأنها مؤشر أولي لتأثير الطابق النبتي المتوسطي  على بعض الصفات الشكلية للسنديان البلوطي. This study was carried out on Quercus infectoria Oliv. species in five sites of various altitude representing the Mediterranean vegetation zones in the Syrian coastal region, Lattakia governorate during 2009 - 2010. This research shows that there is an effect of Mediterranean vegetation zone on investigated trees in different sites, and there are significant differences in relation to characteristics of tree height and diameter, trunk length, length and diameter of fruit, fruits and cupules weight, catkin length, flowers number in one catkin, leaf length, leaf width, leaf area, canopy and fresh and dry weight of leaves. On the other hand, there was no effect of any Mediterranean vegetation zone on the species and there were not any significant differences in relation to the characteristics of height and girth of cupule, length of leaf stalk, humidity percentage of leaves and flowering period. It could be deduced that there were changes in vegetation growth of studied trees in different sites which appeared to be a primary indication of the impact of the Mediterranean vegetation zone on morphological characteristics of Quercus infectoria Oliv.(Gall oak).